Is There a Female Protective Effect Against Attention-Deficit/Hyperactivity Disorder? Evidence From Two Representative Twin Samples - Taylor, Mark J. (J Am Acad Child Adolesc Psychiatry, 2016)
OBJECTIVE: Attention-deficit/hyperactivity disorder (ADHD) is more frequent in males than in females. The “female protective effect” posits that females undergo greater exposure to etiological factors than males in order to develop ADHD, leading to the prediction that relatives of females with ADHD will display more ADHD behaviors. We thus tested whether cotwins of females displaying extreme ADHD traits would display more ADHD traits than cotwins of males displaying extreme ADHD traits. METHOD: Parents of approximately 7,000 pairs of nonidentical twins in Sweden, and approximately 4,000 pairs of twins in England and Wales, completed dimensional assessments of ADHD traits. Probands were selected on the basis of scoring within the highest 10% of the distribution in each sample. Dimensional scores of cotwins of probands, as well as the categorical recurrence rate, were investigated by proband sex. RESULTS: Cotwins of female probands displayed higher mean ADHD trait scores (mean = 0.62−0.79) than cotwins of male probands (mean = 0.38−0.55) in both samples. This trend was significant in the Swedish sample (p < .01) and when the 2 samples were merged into a single, larger sample (p < .001). When the samples were merged, there was also a significant association between proband sex and cotwin’s categorical status, with more cotwins of female probands also being probands than cotwins of male probands. CONCLUSION: These findings support a female protective effect against ADHD behaviors, suggesting that females require greater exposure to genetic and environmental factors associated with ADHD in order to develop the condition.